tell fast solution of the equation (2y+1)/3=3
Answers
Answered by
2
Ans is 3.3
mark me as a brain list
Answered by
0
The correct answer is 4
Step-by-step explanation:
(2y + 1)/ 3 = 3
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3=>2y + 1 = 9
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3=>2y + 1 = 9=>2y = 9 - 1
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3=>2y + 1 = 9=>2y = 9 - 1=>2y = 8
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3=>2y + 1 = 9=>2y = 9 - 1=>2y = 8=>y = 8 / 2
(2y + 1)/ 3 = 3=>2y + 1 = 3 × 3=>2y + 1 = 9=>2y = 9 - 1=>2y = 8=>y = 8 / 2=>y = 4
Similar questions